Dual Band Ring Shaped Dielectric Resonator Based Radiator with Left and Right Handed Sense Circularly Polarized Features. Issue 5 (3rd September 2021) - Sharma, Anand; Ranjan, Pinku; Sikandar,
Abstract : In this communication, ring dielectric resonator antenna is structured and investigated. Dual interrelated circular ring is used to stimulate the ring ceramic material. Three essential appearances of proposed radiator are: (a) interrelated circular ring is used to excite HEM11δ and TE01δ mode in ring-shaped ceramic; (b) T-shaped microstrip line along with linked circular ring is helpful to create CP waves in both operating frequency ranges; and (iii) proposed radiator supports LHCP and RHCP waves in lower and upper frequency range, respectively. Experimental data confirm that proposed antenna works over two frequency ranges i.e. 2.28–2.93 GHz and 4.26–4.65 GHz, respectively. CP waves are also supported in both lower and upper working frequency ranges i.e. 2.55–2.87 GHz and 4.41–4.65 GHz, respectively. This aerial is employable for WLAN (2.5 GHz) and INSAT (4.4 GHz) applications.